Generator polynomial estimation of LFSR sequence based on GFFT - Lihua SHEN (Dianxin kexue)
The problem addressed here is generator polynomial estimation of linear feedback shift register (LFSR) sequence.An algorithm based on the Galois field Fourier transform (GFFT) was proposed.The relationship between non-zero points in GFFT of LFSR sequence and zero points in generator polynomial of LFSR sequence was illustrated firstly.Then the generator polynomial of LFSR sequence was fast estimated based on that property,and the improved method in noisy environment was proposed at last.Validity of the algorithm is verified by the simulation results,and the computational load is illustrated.The computational efficiency of the proposed algorithm is higher than that of the existing algorithms.